The Proust Machine: What a Public Science Event Tells Us About Autobiographical Memory and the Five Senses - Ernst, Alexandra; Bertrand, Julie M. F.; Voltzenlogel, Virginie; Souchay, Céline; Moulin, Christopher J. A. (Frontiers in Psychology, 2021)
Our senses are constantly stimulated in our daily lives but we have only a limited understanding of how they affect our cognitive processes and, especially, our autobiographical memory. Capitalizing on a public science event, we conducted the first empirical study that aimed to compare the relative influence of the five senses on the access, temporal distribution, and phenomenological characteristics of autobiographical memories in a sample of about 400 participants. We found that the access and the phenomenological features of memories varied as a function of the type of sensory cues, but not their temporal distribution. With regard to their influence on autobiographical memory, an overlap between some senses was found, with on one hand, olfaction and taste and, on the other, vision, audition, and touch. We discuss these findings in the light of theories of perception, memory, and the self, and consider methodological implications of the sensory cuing technique in memory research, as well as clinical implications for research in psychopathological and neuropsychological populations.